Pengaruh latihan keseimbangan dan daya tahan aerobik terhadap akurasi menembak atlet 10 meter air pistol perbakin rinjani NTB - Naufal Arif Alwana; Lalu Suprawesta; Jamaludin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to determine the effect of balance training and aerobic endurance on the shooting accuracy of 10 meter air pistol athletes. The research method used a quasi-experimental design with a two-group pretest-posttest approach. The subjects were 10 athletes from Perbakin Rinjani NTB, divided into two groups: the balance training (core stability) group and the aerobic endurance training (fartlek) group. The training program was conducted for 5 weeks with a frequency of 4 times per week. Shooting accuracy data were collected through the standard ISSF 10 meter air pistol scoring test (60 shots). Data analysis used paired sample t-test, independent sample t-test, and Cohen's d effect size. The results showed that: (1) There was a significant effect of balance training on improving shooting accuracy (p=0.003; effect size=0.896). (2) There was a significant effect of aerobic endurance training on improving shooting accuracy (p=0.005; effect size=0.938). (3) There was no significant difference in the effect between the two types of training on shooting accuracy (p=0.760). The conclusion of this study is that both balance and aerobic endurance training are equally effective in improving the shooting accuracy of 10 meter air pistol athletes and can be integrated into training programs.